Histochemical studies on the subcommissural organ of the pig - KUMAR, P; KUMAR, PAWAN (The Indian Journal of Animal Sciences, 2013)
The present study, conducted on 10 healthy adult pigs of local mixed breed, revealed distribution ofmucopolysaccharides, lipids and proteins in ependyma and hypendyma of the subcommissural organ. Periodic acidSchiff’s reaction demonstrated by McManus’ method was present in different components of ependymal cells, andhypendymal cells with more affinity in the blood capillaries of the organ and indicated presence of glycogen. Aldehydethionin PAS activity was mainly localized towards supranuclear portion of the ependymal cells and the blood capillariesof the hypendyma. PAS Alcian blue demonstrated negligible concentration of acidic mucopolysaccharides whereas thedistribution of neutral mucopolysaccharides was similar to that of PAS technique. Neutral and Sudanophilic lipids werelocalized in the form of very small sized droplets and fine dust particles towards base of the ependyma, respectively.The SCO secretions towards free ventricular surface were qualitatively proteinaceous in nature.